Assistance in the Development of Palm Tree-Based Creative Products as an Attraction for Agrotourism in Kekait Village - Lalu Mohamad Iswadi Athar; Zihori Maulida (Karuna: Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
The village of Kekait in West Lombok Regency possesses significant potential for agro-tourism development through the utilization of sugar palm (Arenga pinnata) as its main commodity. However, this potential remains underdeveloped due to limited product innovation, inadequate packaging quality, and a lack of accompanying cultural narratives that can enhance product value. This community service activity aimed to increase the added value of palm-based products by facilitating design innovation and incorporating local wisdom-based storytelling. The method applied was a participatory empowerment approach, combining technical training with hands-on mentoring. Over two months, the program included practical sessions on packaging development, narrative creation, and product prototyping. The results show that the local community successfully adopted eco-friendly kraft paper packaging, designed with Sasak motifs, and implemented product labels that contained educational and cultural narratives. This intervention increased both product attractiveness and economic potential within the local tourism market. The activity concludes that culture-based empowerment can be a transformative strategy for supporting creative economies in rural areas. Further support is recommended in the form of institutional strengthening and access to digital marketing platforms to sustain and scale the initiatives.